2019
DOI: 10.3389/fonc.2019.00135
|View full text |Cite
|
Sign up to set email alerts
|

Repurposed Biguanide Drugs in Glioblastoma Exert Antiproliferative Effects via the Inhibition of Intracellular Chloride Channel 1 Activity

Abstract: The lack of in-depth knowledge about the molecular determinants of glioblastoma (GBM) occurrence and progression, combined with few effective and BBB crossing-targeted compounds represents a major challenge for the discovery of novel and efficacious drugs for GBM. Among relevant molecular factors controlling the aggressive behavior of GBM, chloride intracellular channel 1 (CLIC1) represents an emerging prognostic and predictive biomarker, as well as a promising therapeutic target. CLIC1 is a metamorphic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 227 publications
(297 reference statements)
1
18
0
Order By: Relevance
“…In an independent study, CLIC1 partially decreased the antineoplastic effects of metformin and upregulation of CLIC1 increased drug sensitivity ; this again proves CLIC1 can be a therapeutic target for various tumors. A recent study also showed that several drugs of biguanidine class, including metformin, act via CLIC1 (Barbieri et al, 2019). Metformin is presented as a wonder drug in several pathological conditions such as diabetes, and if CLIC1 directly interacts with metformin, it could possibly provide the "elusive" mechanism of action for the drug.…”
Section: Clic1mentioning
confidence: 99%
“…In an independent study, CLIC1 partially decreased the antineoplastic effects of metformin and upregulation of CLIC1 increased drug sensitivity ; this again proves CLIC1 can be a therapeutic target for various tumors. A recent study also showed that several drugs of biguanidine class, including metformin, act via CLIC1 (Barbieri et al, 2019). Metformin is presented as a wonder drug in several pathological conditions such as diabetes, and if CLIC1 directly interacts with metformin, it could possibly provide the "elusive" mechanism of action for the drug.…”
Section: Clic1mentioning
confidence: 99%
“… NaV1.1 and NaV1.6 play role in cytokines release in glial cells [ 50 , 51 ] TRPM3 GBM cell lines High expression of TRPM3 linked to decreased median survival [ 50 , 52 ] P2RX4 Human glioma High expression of P2RX4 linked to decreased median survival Silencing suppresses glioma cell growth through BDNF/TrkB/ATF4 signaling pathway [ 50 , 53 ] CLCN3 GBM cell lines Reduced expression of CLCN3 inhibits migration of GBM cells CLCN3 suppression can sensitize glioma cells to cisplatin through lysosomal dysfunction [ 54 , 55 ] CLCN6 Human Glioma Down regulated in human glioma, significantly increased risk of death. [ 54 ] CLIC1 Human Glioma GBM cell lines Glioma stem cell CLICL1 is up-regulated in human glioma, conferred poor overall survival CLIC1 silencing reduced proliferative, clonogenic, and tumorigenic capacity of stem/progenitor cells Inhibition of CLIC1 at G1/S transition by metformin is a has an antiproliferative effect in glioblastoma Biguanide inhibition impairs GSC viability, invasiveness, and self-renewal [ 54 , 56 , 57 , 58 ] CLIC4 Human Glioma GBM cell lines Down regulated in human glioma, si...…”
Section: Ion Channels In Gliomamentioning
confidence: 99%
“…Since CLIC1 is upregulated in many types of human cancers and selectively targeted to the plasma membrane in tumor cells, it can be a promising target for the anticancer treatment of invasion and metastasis. Notably, the CLIC1 gene is highly conserved among tumors with only 2% of patients harboring missense or nonsense mutations, indicating that its role in tumorigenesis is more related to its membrane localization-associated activity than to mutations (45). Gurski et al reported that in renal cell carcinoma, CLIC1 cooperates with integrin v3 and fibronectin to stabilize invadopodia for tumor invasion by regulating myosin light chain kinase (MYLK) (46).…”
Section: Discussionmentioning
confidence: 99%